KAJIAN SPIRITUAL INTELLIGENCE TERHADAP TAX COMPLIANCE PADA USAHA KECIL MENENGAH Studi Kasus Penggilingan Beras UD. H - Kartika Sari Hariyanto; Wiyono Pontjoharyo (Perpustakaan Universitas Surabaya, 2018)
Spiritual Intelligence can influence a person's decision making. The purpose of this research is to know the role of Spiritual Intelligence toward tax compliance on small, medium business owner. This research uses qualitative approach. This study was conducted using interviu method, observation, and data analysis. Objects used in this research is business entity engaged in rice milling in Jember. The results of the analysis and discussion show that spiritual intelligence plays a role in the tax compliance carried out by business entities, but not all points in spiritual intelligence proposed by Zohar & Marshall (2000) play a role in tax compliance, self awareness, vision and value led, field independent, and humility that plays role in tax compliance. Spiritual intelligence will be oriented to the public interest and bravely against the flow of non tax compliance so that those with high spiritual intelligence will obey taxes. There are other factors that affect the tax compliance in UD. H. Not feeling the benefits of tax payments and distrust of government giving influence to owners. Mrs. L do not want to play a role in the public interest and this makes the humility points on testing intelligence spirituality not being met.